2004
DOI: 10.1152/japplphysiol.00435.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms involved in branching morphogenesis of theDrosophilatracheal system

Abstract: Cabernard, Clemens, Marc Neumann, and Markus Affolter. Cellular and molecular mechanisms involved in branching morphogenesis of the Drosophila tracheal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…It was also shown that the FGFR signaling pathway is crucial for tracheal cell migration, as MARCM clones mutant for the Drosophila btl/FGFR or for certain downstream effectors of the FGFR signaling pathway remain in the proximal region of the air sac primordium (arrowhead in Figure 2F) and never colonize the migrating tip of the primordium (Cabernard et al 2004). In an attempt to isolate genes involved in tracheal cell migration, mutant lines displaying a migration defect with ,40% of the MARCM clones present at the air sac distal tip were kept for further analysis.…”
Section: Resultsmentioning
confidence: 98%
“…It was also shown that the FGFR signaling pathway is crucial for tracheal cell migration, as MARCM clones mutant for the Drosophila btl/FGFR or for certain downstream effectors of the FGFR signaling pathway remain in the proximal region of the air sac primordium (arrowhead in Figure 2F) and never colonize the migrating tip of the primordium (Cabernard et al 2004). In an attempt to isolate genes involved in tracheal cell migration, mutant lines displaying a migration defect with ,40% of the MARCM clones present at the air sac distal tip were kept for further analysis.…”
Section: Resultsmentioning
confidence: 98%
“…The cellular events leading to distinct steps in branching morphogenesis are best understood in the Drosophila tracheal system [4,6,28]. In brief, the onset of fly tracheal development starts at 5 h after egg-laying (AEL) with formation of ten tracheal sacs on each side of the embryo by invagination of the surface ectoderm.…”
Section: Migration Cell Rearrangement and Change Of Cell Shapementioning
confidence: 99%
“…At 7 h AEL, primary branches start to form by invaginating or budding in six different but stereotypical directions. At each bud site, two cells migrate out of the sac, followed by a small number [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of cells. As they migrate, cells of the primary branch elongate and intercalate such that their initial side-by-side positioning is rearranged to an end-to-end configuration, with the lumen of resultant tubes enveloped by one single cell.…”
Section: Migration Cell Rearrangement and Change Of Cell Shapementioning
confidence: 99%
See 2 more Smart Citations